Collaborative team approaches to supporting inclusion of children with disability in mainstream schools: A co-design study. (July 2022) - Garcia-Melgar, Ana; Hyett, Nerida; Bagley, Kerryn; McKinstry, Carol; Spong, Jo; Iacono, Teresa
Abstract: Background: Collaborative consultation involving educational staff, allied health professionals and parents working towards goals for children with disability is considered best practice in inclusive education. However, challenges can hinder effective collaboration, thereby potentially limiting child outcomes. Aims: The study aims were to (a) explore the experiences of teachers, teacher assistants, allied health professionals, and parents engaging in collaborative teamwork to support inclusion of children with disability in mainstream primary schools, and (b) identify key factors influencing effective teamwork and the design of support strategies. Methods and procedures: A co-design research method emulated collaborative consultation and authentic stakeholder teamwork. Data were from a series of six co-design workshops (15 h); discussions were audio-recorded and transcribed verbatim. An interpretive descriptive method of thematic analysis resulted in four key themes. Outcomes and results: Critical factors that influenced collaborative teamwork were access to diagnosis and funding, mechanisms for team communications, practical ways of working together, and shared understandings of inclusion. Conclusions and implications: Stakeholder teams require effective communication mechanisms and practical ways of working together within and outside of classrooms. Shared understandings of inclusion provide a foundation for collaboration, requiring access to professional development to ensure teamwork is informed by best inclusive education practice. Highlights: Collaborative consultation to support inclusion of students with disability in mainstream primary schools were explored. Regular, consistent, and timely communication, practical ways of working together, and shared understandings were critical. Best practice and theory in school inclusion inform effective teamwork across education and allied health staff, and parents.